The multifaceted role of the inferior colliculus in sensory prediction, reward processing, and decision-making - Xinyu Du; Haoxuan Xu; Peirun Song; Yuying Zhai; Hangting Ye; Xuehui Bao; Qianyue Huang; Hisashi Tanigawa; Zhiyi Tu; Pei Chen; Xuan Zhao; Josef P Rauschecker; et al. (eLife)
The inferior colliculus (IC) has traditionally been regarded as an important relay in the auditory pathway, primarily involved in relaying auditory information from the brainstem to the thalamus. However, this study uncovers the multifaceted role of the IC in bridging auditory processing, sensory prediction, and reward prediction. Through extracellular recordings in monkeys engaged in a sound duration-based deviation detection task, we observed a 'climbing effect' in neuronal firing rates, indicative of an enhanced response over sound sequences linked to sensory prediction rather than reward anticipation. Moreover, our findings demonstrate reward prediction errors within the IC, highlighting its complex integration in auditory and reward processing. Further analysis revealed a direct correlation between IC neuronal activity and behavioral choices, suggesting its involvement in decision-making processes. This research highlights a more complex role for the IC than traditionally understood, showcasing its integral role in cognitive and sensory processing and emphasizing its importance in integrated brain functions.